The Proletarianization of the Professoriate and the Threat to Free Expression, Creativity, and Economic Dynamism. Issue 3 (2nd July 2020) - Wisman, Jon D.; Duroy, Quentin
Abstract: Over the past four decades, forces have been set in motion that are proletarianizing professors—reducing their control over their workplaces. This has been in part propelled by a resurgence of laissez-faire doctrine that has legitimated public policies which have fueled soaring inequality. This article addresses the threat to freedom and economic dynamism posed by the debasement of professors by examining six forces that are driving the proletarianization of the professoriate: the replacement of tenured with contingent faculty, an expansion of for-profit colleges and universities, the rise of online education, the introduction of annual evaluations and merit pay, the development of outcomes assessment, and the increased reliance on external research funding. The essay then surveys how laissez-faire doctrine and rising inequality have led to cuts in government funding for higher education, have placed an increased emphasis on providing student consumers with vocational training as opposed to a liberal education, and have reshaped higher education through the introduction of corporate values within universities' systems of governance. The article concludes with reflections on the evolution of the status of professors in higher education as a symptom of the betrayed promises for personal and social life held forth by economic abundance following WWII.